It's Our Convention: Use It or Lose It? - Peter Mittler (Disability, CBR and Inclusive Development, 2012)
Unless action is taken now, at national and local levels, to ensure that the world’s one billion people with disabilities derive real and lasting benefits, the United Nations Convention on the Rights of Persons with Disabilities is in danger of being consigned to the graveyard of missed opportunities. Although many governments have signed and ratified the Convention, evidence of actual implementation is an immediate priority, especially in the midst of a global recession. The scene is now set for governments to bring their policies into line with the principles and Articles of the Convention and to provide regular reports to the Disabled Persons’ Committee of the United Nations High Commission on Human Rights. Use of the internet can ensure that accountability is made public and includes the full participation of people with disabilities.